Profitability, operating efficiency and capitalization of the portuguese banking system (1992-2009) - Santos, Mário Coutinho dos (2021)
In this article, we conduct an empirical comparative analysis of the Portuguese Banking System (PBS) during the 1993-2009 period. Using a dataset drawn from the Organisation of Economic Cooperation and Development’s (OECD) Banking Statistics – the Financial Statements of banks database, we examine the performance, in terms of the profitability, operating efficiency, and the capitalization of the PBS, in comparison to a sample of euro area banking systems. We found concerning profitability that PBS outperformed in terms of ROA, but underperformed relative to ROE. It outperformed in terms of operating and interest income, cost to income, and net interest margin efficiency. It did not perform differently in terms of the efficiency of operating and interest expenses. It was less exposed to liquidity risk, but more exposed to credit risk, and was undertaxed relative to its control sample peers. Bookvalue capital ratios document that the PBS was overcapitalized, but undercapitalized in terms of the regulatory capital ratio.